Synthesis, spectroscopic and structural characterizations and in vitro antimycobacterial activity of silver(I) complexes with sulfapyridine (SPY) and sulfamerazine (SM) - Amaral, Thaeny Costa; Glanzmann, Nícolas; da Silva, Adilson D.; Pereira, Gabriele de M.; Corbi, Pedro P.; Canales, Christian S.C. [UNESP]; Pavan, Fernando R. [UNESP]; Oliveira, Kaíque A.D.; Cuin, Alexandre (Elsevier, 2024)
Sulfonamides (sulfas) are a specific class of organic compounds that possesses antibacterial, anti-inflammatory, antiviral and antitumor activities. This class of molecules is also used in the synthesis of silver(I) complexes, which usually present significant biological activity as antimicrobial agents. In this context, the present work describes the synthesis, structural characterization and antibacterial assays of two silver(I) complexes with the sulfa drugs sulfapyridine (SPY) and sulfamerazine (SM). Chemical analyses and high-resolution mass spectrometric studies led to 1:1 metal/ligand compositions, suggesting the minimal formulas C11H10N3O2SAg·2H2O for AgSPY and C11H11N4O2SAg·2H2O for AgSM. Spectroscopic techniques such as 1H, 13C and {1H–15N} nuclear magnetic resonance (NMR), and also infrared measurements (IR) suggest the coordination of the ligands to silver(I) ions by the nitrogen atom of the SO2N moiety for both complexes. Crystal structures of AgSPY and AgSM were solved and refined by X-ray powder diffraction studies, where dimeric structures with Ag(I) ions bridging between two ligand molecules by the usual eight membered ring [AgNCN]2 and strong argentophilic interactions were observed. Minimum Inhibitory Concentration (MIC90) assays showed the promising activities of the free sulfonamides and the respective complexes against Mycobacterium tuberculosis H37Rv. MIC90 values, in µmol L–1, were 2.47, 3.60, 1.33 and 1.61 for SPY, AgSPY, SM and AgSM, respectively. The obtained MIC90 values were lower than those found for silver sulfadiazine and silver nitrate in the same experimental conditions.
Keywords: Mycobacterium; Powder x-ray diffraction; Silver(I); Sulfamerazine; Sulfapyridine; Tuberculosis